At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
4x² - 11x = 3
4x² - 11x - 3 = 0
4x² -12x + x - 3 = 0
4x (x - 3) + 1(x - 3) = 0
(x - 3) (4x + 1) = 0
Using zero product property,
Either,
x - 3 = 0
x = 3
Or,
4x + 1 = 0
4x = -1
x = -1/4
4x² - 11x - 3 = 0
4x² -12x + x - 3 = 0
4x (x - 3) + 1(x - 3) = 0
(x - 3) (4x + 1) = 0
Using zero product property,
Either,
x - 3 = 0
x = 3
Or,
4x + 1 = 0
4x = -1
x = -1/4
[tex]4 x^{2} -11x-3=0[/tex]
(4x+1)(x-3)=0
We can solve for x by setting each parentheses equal to 0
x= -1/4
x= 3
(4x+1)(x-3)=0
We can solve for x by setting each parentheses equal to 0
x= -1/4
x= 3
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.